Pengaruh Kepercayaan Diri Dan Semangat Kerja Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervening - Rahmat Laan; Sari Zulfian Hasan (Jurnal Manajemen, 2022)
The purpose of this study was to analyze (1) the significance of the effect of self-confidence on employee performance either directly or through work motivation as an intervening variable; (2) the significance of the effect of morale on employee performance either directly or through work motivation as an intervening variable; The research sample was 89 employees. The sample was determined using the Sampling Table with an error rate of 5%. Data were collected with the main instrument, namely a questionnaire. Data analysis technique using Path Analysis. The results showed that (1) Self-confidence had a significant effect on employee performance but not significant through work motivation as an intervening variable; (2) Work morale has a significant effect on employee performance but is not significant through work motivation as an intervening variable.